Formation of Literary Image of I. M. Muravyov-Apostol - A. A. Okhremenko (Научный диалог)
The formation of the literary image of Ivan Matveyevich Muravyov-Apostol is discussed, who entered the history of Russian literature as the author of a journalistic series “Letters from Moscow to Nizhny Novgorod” and “The Journey in Tauris in 1820.” It is noted that I. M. Muravyov-Apostol is famous for being “a scholar and lover of antiquity.” The author of the article explores the translation activity of I. M. Muravyov-Apostol, his enthusiasm for the work of the Roman poet Horace. It is shown how the translations of satirical works and odes of Horace by Muravyov-Apostol influenced the formation of his literary interests and, accordingly, the creation of the literary image of the writer. The critical works devoted to the translation activity of Muravyov-Apostol are considered. The role of friendship is noted between the writer and G. R. Derzhavin with whom they were united by similar attitude to the literary and civil issues, as well as interest in ancient culture and translation of satirical works and odic poetry of Horace. Excerpts from their correspondence are given, as well as opinions of other writers about the creative activities of Muravyov-Apostol. The author concludes that special influence on the formation of Muravyov-Apostol’s literary image had self-presentation of his translations at meetings of the society “Beseda lyubiteley russkogo slova.”